Pemanfaatan Tanaman dalam Sediaan Kosmetika Sebagai Antioksidan dan Anti-Tirosinase: Narrative Review - Resina Hajar; Fikri Alatas (Universitas Wahid Hasyim Semarang, 2024)
Studies on the antioxidant activity of various plants growing in Indonesia have been widely conducted, however, information relating to testing its activity as an anti-tyrosinase and its formulation in cosmetic preparations is still limited. This literature review explores the use of plants with antioxidant and anti-tyrosinase activity and their development in cosmetic dosage forms. The method for searching references in national and international journals is carried out with the help of the Google Scholar and PubMed search engines published in the last 10 years (2014-2023). After screening by paying attention to inclusion and exclusion criteria, 32 journal articles were used to write this article. Antioxidant and anti-tyrosinase activities are found in almost all parts of the plant, which are generally extracted by maceration with ethanol solvent. Various methods for testing antioxidant activity in vitro are generally based on the presence of a redox reaction between a free radical reagent and an antioxidant which is analyzed spectrophotometrically, while testing anti-tyrosinase activity, is generally tested based on reducing the amount of dopachrome formed in the presence of anti-tyrosinase. The use of plants with antioxidant and anti-tyrosinase activity in cosmetic preparations has been carried out, although it is still limited to conventional preparations, such as creams and gels.